The interplay of DNA methyltransferases and demethylases with tuberization genes in potato (Solanum tuberosum L.) genotypes under high temperature - Dutta, Madhushree; Raturi, Vidhi; Gahlaut, Vijay; Kumar, Akhil; Sharma, Paras; Verma, Vipasha; Gupta, Vijai Kishor; Sood, Salej; Zinta, Gaurav (Frontiers in Plant Science, 2022)
Potato is a temperate crop consumed globally as a staple food. High temperature negatively impacts the tuberization process, eventually affecting crop yield. DNA methylation plays an important role in various developmental and physiological processes in plants. It is a conserved epigenetic mark determined by the dynamic concurrent action of cytosine-5 DNA methyltransferases (C5-MTases) and demethylases (DeMets). However, C5-MTases and DeMets remain unidentified in potato, and their expression patterns are unknown under high temperatures. Here, we performed genome-wide analysis and identified 10 C5-MTases and 8 DeMets in potatoes. Analysis of their conserved motifs, gene structures, and phylogenetic analysis grouped C5-MTases into four subfamilies (StMET, StCMT3, StDRM, and StDNMT2) and DeMets into three subfamilies (StROS, StDML, and StDME). Promoter analysis showed the presence of multiple cis-regulatory elements involved in plant development, hormone, and stress response. Furthermore, expression dynamics of C5-MTases and DeMets were determined in the different tissues (leaf, flower, and stolon) of heat-sensitive (HS) and heat-tolerant (HT) genotypes under high temperature. qPCR results revealed that high temperature resulted in pronounced upregulation of CMT and DRM genes in the HT genotype. Likewise, demethylases showed strong upregulation in HT genotype as compared to HS genotype. Several positive (StSP6A and StBEL5) and negative (StSP5G, StSUT4, and StRAP1) regulators are involved in the potato tuberization. Expression analysis of these genes revealed that high temperature induces the expression of positive regulators in the leaf and stolon samples of HT genotype, possibly through active DNA demethylation and RNA-directed DNA methylation (RdDM) pathway components. Our findings lay a framework for understanding how epigenetic pathways synergistically or antagonistically regulate the tuberization process under high-temperature stress in potatoes. Uncovering such mechanisms will contribute to potato breeding for developing thermotolerant potato varieties.